KEEFEKTIFAN PENGGUNAAN MEDIA VIDEO INTERAKTIF TERHADAP MINAT BACA SISWA KELAS III SD MUHAMMADIYAH IDI TELLO BARU KOTA MAKASSAR - Nurhalisah, Siti; Asnidar, Anin; Rajab, Abd (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The main problem in this study is the low interest in reading among students during learning activities, which is characterized by a lack of enthusiasm, low focus, and minimal initiative in reading.This study used a quantitative approach with a pre-experimental design using a one-group pretest-posttest. The sample consisted of all 23 third-grade students. Data collection techniques included questionnaires and observation sheets, while data analysis was conducted descriptively and inferentially using normality tests, the Wilcoxon Signed Rank Test, and the N-Gain test.The results of the study showed that students' reading interest scores in the pretest stage were in the low category (range 54–64), while the posttest results increased to the high category (range 75–80). The Wilcoxon Signed Rank Test produced a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. In addition, the average N-Gain value of 0.48 is included in the moderate category.Based on the research results, it can be concluded that the use of interactive video media is effective in increasing the reading interest of grade III students at Muhammadiyah IDI Tello Baru Elementary School, Makassar City.